Fermented Thitonia Innovation for Dairy Goat Feed Efficiency in Muda Mandiri Farmer Group, Sungai Pua Sub-District, Agam District - Roni Pazla; El Latifa Sri Suharto; Rahmani Welan; Antonius; Muhammad Zhorif Hidayat; Zaitul Ikhlas; Gusri Yanti; Vito Dwi Purnomo; Rizki Romadhon; Naufal Al Haq (Warta Pengabdian Andalas, 2025)
One of the Muda Mandiri farmer groups located in Nagari Sungai Pua, Sungai Pua District, has 30 Peranakan Etawa goats, and this farmer group consists of 11 farmers. This group is one of the highly developed dairy goat farming businesses in Agam Regency. This community service activity aims to apply fermented tithonia technology as an alternative forage feed for ruminants to improve the feed efficiency of dairy goats. The activity method consists of several steps. First, farmer groups were taught about how to manage forage feed and the benefits of thitonia fermentation. Second, they learned the fermentation process, which starts with chopping tithonia, mixing it with inoculum (L. bulgaricus), adding molasses, and mixing it with bran. This mixture was kept in a container without air exposure for fourteen days. Third, the fermented product was tested directly as feed for dairy goats to determine how palatable it was and how much it impacted milk production. Important results showed that although milk production was almost the same as the previous feed using field grass, fermented tithonia could replace up to 30% of field grass. The farmer does not need to search for grass daily, as time and effort are spent more efficiently providing feed. In conclusion, fermented tithonia is an effective and easy-to-implement technology to help dairy goat farmers obtain a more efficient alternative feed, which eases their workload.